P113 Accuracy of a new rapid test assay for monitoring adalimumab levels. (25th January 2019) - Afonso, J; Rocha, C; Lago, P; Arroja, B; Vieira, A I; Dias, C C; Magro, F
Abstract: Background: Low serum concentrations at trough levels have been related with loss of response in inflammatory bowel disease (IBD) patients under Adalimumab (ADA) therapy. Most of the methods commercially available in the market for the quantification of ADA are ELISA-based, with a turnaround time of approximately 8 h, delaying the target dosage adjustment to following infusion. A new rapid test device (RT-ADA) was recently launched for monitoring serum ADA levels. The aim of this study was to evaluate the performance of a new rapid test for ADL quantification by comparing it with three well-established methods. Methods: Sera from 120 IBD patients undergoing ADA therapy were quantified by four assays: rapid test lateral flow Quantum Blue® from Buhlmann (RT-ADA) and three ELISA formats: commercials assay from Immundiagnostik (ELISA A) and from R-Biopharm (ELISA B) and an in-house assay. Moreover, donor's serum samples were spiked with known concentrations of ADA and the percentage of recovery of each assay was evaluated. Results: Spiked samples showed an excellent Intraclass Correlation Coefficient (ICC) between theoretical and measured concentrations for all the assays 0.927, 0.984, 0.982 and 0.989 and a good recovery 111%, 113%, 86%, 110%, respectively, ELISA A, ELISA B, RT-ADA, and in-house ELISA. Regarding the clinical samples, the ICC of the RT-ADA assay vs. the three ELISA-based established methods was 0.590, 0.761, and 0.864, respectively, RT-ADA/ELISA A, RT-ADA/in-house ELISA and RT-ADA/Elisa B. When using different cut-offs for a qualitative comparison, RT-ADA showed accuracy between 73 and 89% and the kappa statistics revealed mostly a good agreement (0.492 and 0.682). Conclusions: The new RT-ADA assay, which is able to deliver results within 15 min, can safely replace the commonly used ELISA-based ADA quantification kits and it is reliable alternative to these methods. This new assay is perfect for immediate concentration adjusted dosing avoiding delays cause by ELISA assays with a turnaround time of approximately 8 h.